Common genetic variants have associations with human cortical brain regions and risk of schizophrenia. Issue 5 (3rd April 2019) - Bi, Xuan; Feng, Long; Wang, Shiying; Lin, Zijie; Li, Tengfei; Zhao, Bingxin; Zhu, Hongtu; Zhang, Heping
Abstract: Schizophrenia is a highly heritable mental disorder and is reported to be associated with measurements in cortical regions of the human brain. In this study, we considered genome‐wide association studies to uncover genetic effects on cortical regions and prodromal symptoms of schizophrenia. Specifically, area, thickness, and volume of 66 cortical regions derived from magnetic resonance imaging scans of 1, 445 children and adolescents from the Philadelphia Neurodevelopmental Cohort were studied. Two common variants were identified as being associated with two prefrontal cortical regions (one significant variant rs11601331 on chromosome 11p11 for right rostral middle frontal gyral area, p = 1.97 × 10 −8 ; one suggestive variant rs2345981 on chromosome 6q11 for left frontal pole gyral volume, p = 2.07 × 10 −7 ), where the significance of rs11601331 was independently replicated on the Pediatric Imaging, Neurocognition, and Genetics study of size 1, 239 ( p = 9.19 × 10 −3 ). Moreover, genetic effects on schizophrenia were investigated based on a sample of 8, 719 subjects. The two identified variants rs11601331 and rs2345981 showed significant association with the longest prodromal symptoms duration ( p = 0.048 and p = 0.027, respectively).